Games and simulations in online learning research and development frameworks - Gibson, David; Aldrich, Clark, 1967-; Prensky, Marc (Information Science Pub., 2007)
"This book examines the potential of games and simulations in online learning, and how the future could look as developers learn to use the emerging capabilities of the Semantic Web. It explores how the Semantic Web will impact education and how games and simulations can evolve to become robust teaching resources"--Provided by publisher.